Ungheresi sulla tradotta: l’Italia meta di viaggio verso il fronte nella prima guerra mondiale - Sciacovelli, Antonio (Verbum – Analecta Neolatina, 2019)
The novel “Doberdo” by Máté Zalka, a literary work that strongly captured the attention of the Hungarian readers in the second post-war period, contributing to the “popularization” of some Italian place names clearly present in the Hungarian imagery (Doberdo, Isonzo and Piave are the most frequent, even in some popular songs still very famous today), begins with a journey on the ridotta (military train), a journey with a not always known destination, from which one is not always sure to return, a journey that creates a period of suspension before the imminent war. The vision of the Italian front (the Carso) during the First World War is one of the reasons, in Hungarian literature, for a radical change from the previous experiences of Hungarian writers in Italy: starting from 1915 they go towards the borders of Italy to “defend the homeland”, to write war correspondences that exalt the warlike virtue of the “KuK” army (but above all of the royal ones), to describe the sometimes disastrous state in which the bombed cities find themselves almost to the ground (as in the case of Gorizia). How much Italy has changed compared to the previous visions of the Italo-maniacs, those who had found their new homeland in Rome, Florence, Venice!